Effects of planting practices and nitrogen management on grain sorghum production - Maiga, Alassane (Kansas State University, 2012)
Sorghum [Sorghum bicolor (L.) Moench] is a relatively drought- and heat-tolerant cereal crop. Global demand and consumption of agricultural crops for food, feed, and fuel is increasing at a rapid pace. To satisfy the growing worldwide demand for grain, production practices must be well optimized and managed. The objectives of the present study were: to optimize sorghum production by determining the best management practices (planting date, row spacing, seeding rate, hybrid maturity) for growth and yield, to evaluate the agronomic responsiveness of grain sorghum genotypes to nitrogen (N) fertilizer and to develop a partial financial budget to N fertilizer application based on best management practices. In order to meet these objectives, field experiments were conducted in 2009, 2010 and 2011 at Manhattan, Belleville, Ottawa, Hutchinson, Hays, at KSU Experiment Stations and Salina, and Randolph at Private Farms. Results indicated that early planting date (late May) and narrow row spacing (25 cm) providing the most equidistant spacing, produced better plant growth, light interception, yield components (number of grains per panicle, 300-grain weight), and biological yield. Results indicated that with increasing N rate, there was a proportional increase in chlorophyll SPAD meter reading, leaf color scores and number of green leaves. There was a significant difference among hybrids for N uptake, NUE and grain yield. However, there was no effect of N and no interaction between N and hybrid on grain yield. Over all, the genotypes with high NUE also had higher grain yield. Economic analysis using partial budget indicated that all N levels had positive gross benefit greater than control at all locations. However, the response varied across locations. Our research has shown that sorghum responds to changing management practices and opportunities exist to increase grain yield by optimizing planting date, seeding rate, row spacing, N application and selection of genotypes.
Keywords: Planting practices, nitrogen management; Nitrogen management; Agronomy (0285)